Bulk Electrocatalytic NADH Cofactor Regeneration with Bipolar Electrochemistry. Issue 3 (23rd November 2021) - Zhang, Chunhua; Zhang, Huiting; Pi, Junying; Zhang, Lin; Kuhn, Alexander
Abstract: Electrochemical regeneration of reduced nicotinamide adenine dinucleotide (NADH) is an extremely important challenge for the electroenzymatic synthesis of many valuable chemicals. Although some important progress has been made with modified electrodes concerning the reduction of NAD +, the scale‐up is difficult due to mass transport limitations inherent to large‐size electrodes. Here, we propose instead to employ a dispersion of electrocatalytically active modified microparticles in the bulk of a bipolar electrochemical cell. In this way, redox reactions occur simultaneously on all of these individual microelectrodes without the need of a direct electrical connection. The concept is validated by using [Rh(Cp*)(bpy)Cl] + functionalized surfaces, either of carbon felt as a reference material, or carbon microbeads acting as bipolar objects. In the latter case, enzymatically active 1, 4‐NADH is electroregenerated at the negatively polarized face of the particles. The efficiency of the system can be fine‐tuned by controlling the electric field in the reaction compartment and the number of dispersed microelectrodes. This wireless bioelectrocatalytic approach opens up very interesting perspectives for electroenzymatic synthesis in the bulk phase. Abstract : Wireless electrocatalytic regeneration of the enzymatically active cofactor NADH is achieved on functionalized carbon beads suspended in the bulk phase of a bipolar electrochemical cell. The catalytic efficiency can be fine‐tuned by the concentration of suspended particles and the applied external electric field.